Resiliensi Pendidikan Diniyah dalam Menghadapi Covid-19 selama Bulan Ramadhan 2021 - Jalaluddin Jalaluddin (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2021)
Diniyah education has been implemented by all educational institutions in Indonesia, starting from the lowest level, namely SD/MI to SMA/MA. Initially this diniyah education was implemented in Islamic boarding schools during the month of Ramadan. The aim is to foster morals, character, and strengthen worship for students during the month of Ramadan. The purpose of this study was to identify the role of diniyah education carried out in the world of education during the Covid-19 pandemic. This research method is a literature study method with a qualitative approach. The results showed that the role of diniyah education can be measured through 4 things, namely increasing student religiosity, developing sustainable education and in accordance with the development of the times, being patient with calamities, and increasing husnuzon attitudes in students.